The Molecular Study on the Identity, Genetic Composition, and Phylogenetic Relationships of Carcharhinus (Blainville, 1816) Sharks in the Western Waters of Aceh - Bahri, Samsul; Ruzanna, Arina; Burhanis, Burhanis (Universitas Gadjah Mada, 2025)
The shark genus Carcharhinus faces high exploitation pressure in the Western Waters of Aceh, while comprehensive genetic data to support conservation remains limited. This study aimed to identify species, analyze nucleotide composition, and reconstruct the phylogenetic relationships of Carcharhinus sharks using the Cytochrome c oxidase subunit I (COI) gene as a molecular marker. A total of 14 tissue samples were collected from three fish landing sites: Aceh Jaya, West Aceh, and Southwest Aceh. Standard procedures included DNA extraction, PCR amplification, sequencing, and bioinformatic analysis using BLAST for identification and MEGA for phylogenetic analysis via the Neighbor-Joining method. Molecular identification successfully confirmed the presence of six species: Carcharhinus falciformis (n=7), C. sorrah (n=3), C. brevipinna (n=1), C. amboinensis (n=1), C. amblyrhynchos (n=1), and C. limbatus (n=1), with identity matches ranging from 99.23-100%. Nucleotide composition analysis revealed a consistent bias towards Adenine and Thymine bases (AT-rich), a common characteristic of the elasmobranch mitochondrial genome. The reconstructed phylogenetic tree demonstrated that each species formed a solid monophyletic group with high bootstrap support. The analysis also confirmed C. brevipinna and C. amboinensis as sister taxa. No clear geographic population structure was found for widespread species, indicating high population connectivity within these waters. This molecular baseline data is crucial for supporting evidence-based fisheries management and conservation strategies for threatened shark species in Indonesia.